An elementary transfers procedure for sharing the joint surplus in games with externalities - Joss Erick Sánchez-Pérez (Estudios Económicos, 2023)
Sánchez-Pérez (2017, Theorem 3) presents an analytic characterization for all solutions for games with externalities that satisfy the axioms of linearity, symmetry, and efficiency. The main goal of this paper is to recast such formulation to a more intuitive interpretation. In particular, we are interested in an interpretation based on the idea of transfers among players.